A Review on Solar PV Based Grid Connected Microinverter Control Schemes and Topologies - Premkumar, Manoharan; Karthick, Kanagarathinam; Sowmya, Rayichandran (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
From the last decade, there is an increase in the demand of electricity, this will causing depletion in the fossil fuels which results increase in cost. So the focus is shifted to use of renewable energy sources along with the only utility grid but it is not sufficient to supply the power different loads. To overcome these problems, micro-grid (MG) is introduced and it is powered by renewable distributed generation (DG) systems, such as, micro turbines, fuel cells, PV and wind generation due to the limited fossil fuel. Out of the above sources, solar energy provides extraordinary benefits including environmental friendly, surplus availability and low installation cost due to the advanced technology and mass production. The solar grid connected micro inverters gain lot of intention in past few years due to its simple construction, reliability and endurability. Moreover, the grid connected micro inverter has high reliability and it can operate in abnormal conditions also like variations in voltage and current. The micro-inverter has attracted recent market success due to unique features such as lower installation cost, improved energy harvesting, and improved system efficiency. This article gives detailed review on different topologies for grid connected solar PV micro-inverter and suggests the reliable, suitable and efficient topology for micro-inverter.Article History: Received Dec 16th 2017; Received in revised form May 14th 2018; Accepted June 1st 2018; Available onlineHow to Cite This Article: Premkumar, M., Karthick, K and Sowmya, R. (2018) A Review on Solar PV Based Grid Connected Microinverter Control Schemes and Topologies. Int. Journal of Renewable Energy Development, 7(2), 171-182.https://doi.org/10.14710/ijred.7.2.171-182Â